The Effect of Cabbage Waste Pretreatment on Lignocellulose Content for Bioethanol Production - Dewi, Luthfi Kurnia; Setyobudi, Sadiah Tulus; Kurnianti, Nurul Fajria; Nirwana, Wa Ode Cakra; Andriana, Rifa Rahma (IPTEK The Journal of Engineering, 2024)
Cabbage waste represents a resource rich in lignocellulose, offering substantial potential as a raw material for bioethanol production. However, the nature of lignocellulosic complexes necessitates effective pretreatment strategies to enhance cellulose accessibility. This study aims to determine the effect of pretreatment on cabbage waste on changes in lignocellulosic content before and after pre-treatment to determine the influence of solution concentration and pretreatment duration of cabbage waste on the level of reducing sugars, which will subsequently affect bioethanol fermentation. In this research, cabbage waste was pretreated using H2SO4 1 M and alkaline NaOH 1 M for 1 hour to determine the pretreatment agent that produced the highest cellulose content. Furthermore, the concentration (1 M; 1.5 M; 2 M) and the pretreatment time (1 hour; 1.5 hours; 2 hours) will be varied to produce the highest reducing sugar content, which will be continued to the Simultaneous Saccharification and Fermentation (SSF). The results showed that pretreatment using H2SO4 produced the highest change in cellulose content. Pre-treatment using H2SO4 at a concentration of 1.5 M for 1.5 hours produced the highest reducing sugar concentration of 0.32 g/L. The highest bioethanol content was obtained during fermentation for 72 hours at 22.25%.